(untitled) (International Seven Journal of Health Research, 2024)
INTRODUCTION: It is necessary to understand the principles of chronic ligament injuries involving the ankle, which happen when there is damage or weakening, which can happen due to repeated or untreated injuries (AMODIO, 2013). In general, chronic ligament injuries occur due to recurrent sprains or sprains of the ankle. Ligaments are fibrous tissues that connect bones and provide stability to joints. In the ankle, the ligaments usually affected are the anterior talofibular ligament and the calcaneofibular ligament. METHODOLOGY: This is a literature review, whose databases were taken from the SciELO and PubMed data platforms. The research period was from July 2023, meeting the inclusion criteria, which were articles from the years 2000 to 2023, in Portuguese and English, online texts, and in full texts. The following health descriptors (DeCS) were used as strategies for better evaluation of the texts: "Ligament injury", "Ankle" and "Chronic". RESULTS: Ankle sprains, which are very common in athletes and individuals with an active life, are an injury caused, in most cases, by eversion or inversion of the foot due to sudden and violent movements, which may or may not cause ligament rupture (BARONI, 2010). Acute ankle ligament injuries are common, with the most prevalent being injuries to the lateral ligament complex. In the neutral position, the bony anatomy of the ankle joint is responsible for stability. Bone stability is increased by compressive loads in the body load position. Most lateral ligament injuries of the ankle resolve spontaneously with conservative treatment (LYNCH, 1999), and such conservative treatment leads to the mechanical stability of this joint in a large percentage of cases. (AMODIO, 2013). On the other hand, persistent problems after ankle ligament injuries are not uncommon. After both conservative and surgical treatment, 10% to 30% of patients with lateral ligament injury may present with chronic symptoms (Lynch, 1999). CONCLUSION: By understanding the treatment modalities, it is understood that the chronicity of ankle ligament injuries require surgical treatment in severe cases in an acute way, the cases in which more extensive injuries are involved in time, require different treatment modalities, in order to prevent progression and instability in the patient.